Zakat dalam Prespektif Al-Qur’an (Solusi dalam Pemberdayaan Umat) - M. Muhamad Bajri (Mufham: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
Al-Qur’an as a macro and mikro cosmos guides has given a warning to mankind,that poverty has been exist when mankind stay at this world, evenly the people who know about religions but doesn’t want to help the other who needs help in economicly so that people do disbelieving of religion. Implicitly that Allah’s warning is contain a message that poverty and their wealth will be exist, so mankind can help each other. Poverty as a social phenomenon has emerged with mankind but poverty will continue to be the talk of all walks of life for human beings in the world. This thing happen because every mankind has a desire to live balance between physical needs and spiritually and to make solidarity, serenity among the main requirement is the fulfillment of material. Because of that, the duty of mankind to live their lives in their society is to help each other, especially to a poor people. It is an attempt to realize justice and humanity. Therefore the poverty needs to be destroyed, because the implication from the poverty problem can be involves all aspects of life, forming a complex problem. Besides, one more thing who can be adds to the complexity of the problem is poverty existing which is not too considered about it. The poverty accepted by them as a normal thing, because perhaps that poverty is been going on in the dimension of time and space and unlimited. Because of that there is a people who consider that poverty as a form of persecution against him who gave birth to poverty. Lots of people see apoverty in a wrong way perspective. The first step is carried out when the Qur’an is to straighten misperception. That poverty is one of a basic problem for mankind, so dreadful of the poverty problem through the prophet Muhammad SAW give confirmation of the danger of poverty through his words “pauperism it nearly approached in disbelief “. The poverty also hated by sayyidina Ali bin Abi Thalib R.A. Even his indignation against poverty is pronounced with the expression, if poverty is in human form, surely I will kill him